Adjuvant and first line chemotherapy use for endometrial cancer - Anne Knisely; Yongmei Huang; Yeran Li; Vimalanand S. Prabhu; Jason D. Wright (Elsevier, 2022)
Objective: The objective of this study was to describe patterns of utilization of cytotoxic, hormonal, and immunotherapy in patients with endometrial cancer in the adjuvant setting and at the time of first recurrence. Methods: We identified patients in the IBM MarketScan database with endometrial cancer who underwent hysterectomy from 2011 to 2019. The use of clinically relevant therapeutic agents and combination regimens was determined in the adjuvant setting and at the time of first recurrence. Results: A total of 22,632 patients were identified. Of these, 7,147 patients (31.6%) received adjuvant radiation and 4,381 (19.4%) received adjuvant chemotherapy following surgery. Of those who received adjuvant chemotherapy, the most commonly utilized agents were carboplatin (90.3%), paclitaxel (85.8%), cisplatin (9.4%), docetaxel (9.3%), gemcitabine (3.8%), and doxorubicin (2.0%), while bevacizumab was utilized in 1.5% of patients. A combination of platinum and a taxane were utilized as adjuvant therapy in 88.8% of women. Of the cohort, 1,825 patients (8.1%) recurred, of whom 1,017 patients had already received adjuvant chemotherapy. The median time from hysterectomy to initiation of chemotherapy for recurrence was 13.3 months (IQR: 7.6-23.1 months). Overall, platinum and taxane combination therapy was used in 788 (46.8%) of patients with recurrent disease, platinum alone or with other drugs in 194 (11.5%), taxanes alone or with other drugs in 145 (8.6%), and non-platinum and non-taxane based therapy in 31.3%. Conclusions: Among patients with endometrial cancer who underwent hysterectomy, platinum-taxane combination chemotherapy was used in almost 90% of patients who received adjuvant chemotherapy while nearly 70% of patients who recurred were treated with platinum or taxane based therapy at first recurrence.